Comparison of a latex agglutination test with other serological tests for the measurement of antibodies to Toxoplasma gondii. Issue 11 (November 1984) - Payne, R A; Francis, J M; Kwantes, W
Abstract : One hundred sera from 49 patients with glandular toxoplasmosis were examined by a latex agglutination test, the dye test, an indirect haemagglutination test, and a double antibody sandwich enzyme linked immunosorbent assay (ELISA) for antitoxoplasma IgM. The results support previous findings that the dye test, indirect haemagglutination test, and latex agglutination test measure different antibodies to Toxoplasma gondii. In early glandular toxoplasmosis, when specific IgM was detected, the titres of both the latex agglutination test and the indirect haemagglutination test were lower than the dye test. Repeat specimens from 11 of the patients showed four cases in which the latex agglutination test titres never exceeded 1/256, whereas both the dye test and the indirect haemagglutination test showed significant titres and specific IgM was detected in every case. We conclude that the latex agglutination test should not be used as a substitute for the dye test in the serological diagnosis of glandular toxoplasmosis. All sera giving a positive latex agglutination test result should be referred for further tests. A combination of the dye test and double antibody sandwich ELISA gives the most reliable serological diagnosis of early glandular toxoplasmosis.